Use of the synbiotic VSL#3 and yacon-based concentrate attenuates intestinal damage and reduces the abundance of Candidatus Saccharimonas in a colitis-associated carcinogenesis model. (November 2020) - Cruz, Bruna Cristina dos Santos; Conceição, Lisiane Lopes da; Mendes, Tiago Antônio de Oliveira; Ferreira, Célia Lúcia de Luces Fortes; Gonçalves, Reggiani Vilela; Peluzio, Maria do Carmo Gouveia
Graphical abstract: Highlights: Synbiotic positively modulates hepatic antioxidants enzymes activity in a CAC model. Synbiotic changes the microbial community in a CAC model. Synbiotic reduces relative abundance of Candidatus Saccharimonas in a CAC model. Synbiotic increases the fecal short-chain fatty acids in a CAC model. Abstract: Individuals with inflammatory bowel disease are at high risk of developing colitis-associated cancer; thus, strategies to inhibit disease progression should be investigated. The study aimed to explore the role of the synbiotic (probiotic VSL#3® and yacon-based concentrate) in a colitis-associated carcinogenesis model. IL-10 −/− mice were induced to carcinogenesis with 1, 2-dimethylhydrazine and divided into two experimental groups: control and synbiotic. Manifestations of colitis, colon histology, expression of antioxidant enzymes, production of organic acids and intestinal microbiota were evaluated. The use of the synbiotic showed benefits, such as the preservation of intestinal architecture, increased expression of antioxidant enzymes and the concentration of organic acids, especially butyrate. It was also observed different microbial community profiles between the groups during the study. Together, these factors contributed to mitigate the manifestations of colitis and improve intestinal integrity, suggesting the potential benefit of the synbiotic in intestinal diseases.